Quantum routing of surface plasmons by two quantum dots. Issue 9 (21st May 2019) - Huang, Jin-Song; Zhang, Jia-Hao; Wei, Lian-Fu
ABSTRACT: The quantum routing of single surface plasmons in a system with two metal nanowires coupled to a pair of quantum dots is investigated theoretically. Real-space Hamiltonians are utilized to obtain the surface-plasmon routing probabilities scattered by two quantum dots in four ports of two nanowire waveguides. Numerical results show that the routing capability of the surface plasmons transmitted from the input channel into another channel can be significantly enhanced, by properly adjusting the interdot distance and the dot-plasmon couplings. Moreover, multi-peak Fano-like resonances are exhibited in the scattering spectra due to the quadratic dispersion relations of the nanowire waveguides. Therefore, the proposed double-dot configuration may provide potential applications in controlling the surface-plasmon routing and Fano-like resonance.